A new species of Bryconops Kner (Characiformes: Iguanodectidae) from the Rio Maicuru, lower Amazon basin, Brazil - Silva-Oliveira, Cárlison; Lima, Flávio C. T.; Bogotá-Gregory, Juan D. (Zootaxa, 2018)
A new species of Bryconops is described from the rio Maicuru, a tributary of the left margin of the lower Amazon River, Pará, Brazil. Bryconops chernoffi new species, differs from all its congeners by the presence of an elongated dark patch of pigmentation immediately after the posterodorsal margin of the opercle, running vertically from the supracleithrum to the distal margin of the cleithrum (vs. absence of a similar blotch), and by a dark dorsal fin with a narrow hyaline band at middle portion of dorsal-fin rays (vs. dorsal fin hyaline or with few scattered chromatophores). It differs further from all its congeners, except B. colanegra, by the presence of a blurred black stripe at the anal fin base. It differs from B. colanegra by possessing fewer predorsal scales (8–9 vs. 10–11) and in that the third infraorbital contacts the preopercle ventrally (vs. third infraorbital not contacting preopercle ventrally). The new species is assigned to the subgenus Creatochanes by the number of maxillary teeth, and ossification and denticulation of the gill rakers.